Serge Lifar: the way to the glory - Semenova, V. (ХДАК, 2023)
A Ukrainian choreographer Serzh Lifar is an outstanding ballet dancer, dance theorist, choreographer and teacher. His name is also known as the founder of the neoclassical trend in ballet art. S. Lifar got his choreography background at the Kyiv ballet studio “School of Movement”; by Bronislava Nijinska. Here he mastered the basics of classical dance and got acquainted with modern dance trends. Dedicated work of the future dancer, fantastic love to dance contributed to the transformation of an ordinary young man, who started practicing ballet at the age of 16, into a leading soloist.
Keywords: Лифар Серж, Lifar Serzh